Aplicação dos métodos DRASTIC e POSH para a determinação da vulnerabilidade e perigo à contaminação do Aquífero Utiariti na cidade de Sinop/MT - Silva, Crysthian Roberto Macedo da (2014)
This work was carried out in the city of Sinop, located in the northern center of the state of Mato Grosso, with the objective to assess the risk and vulnerability to contamination of the Utiariti aquifer using the DRASTIC and POSH methods. The geological, pedological, hydrogeological and topographical data used in the application of DRASTIC were compiled from work already undertaken in the area, while data from potential sources of contamination were collected in the area. The vulnerability classes determined by DRASTIC were moderate occurring in 84% of the area and in 16%. In the area exist 12 potential contamination sources, which were classified through the POSH in low, moderate and high. The risk of contamination of the aquifer are moderate, high and very high in both vulnerabilities, where are located the potential sources of the most threatening groundwater contamination. These results may be used to propose preventive and corrective measures aimed at water quality.